Systems thinking for general surveillance programs – using leverage points to guide program management - Ticehurst, Jenifer L.; Kruger, Heleen (Frontiers in Ecology and Evolution, 2023)
With the increasing threat of pests, weeds and diseases to agriculture, the environment and our way of life, governments are becoming more reliant on general surveillance to fill biosecurity surveillance gaps. It is often thought that enabling general surveillance programs simply requires the development of reporting tools and creating awareness of the program among intended target groups. However, this narrow approach may not effectively support a program to meet its goals long-term. We used systems thinking to explore what helps and hinders the design and implementation of general surveillance programs, drawing on international literature and the experiences of people in nine case studies from across Australia and New Zealand. Systems thinking helped identify the components and complex interactions that exist within general surveillance programs. These components are the actors involved and their relationships; infrastructure like reporting tools and resources; formal and informal rules; and the species or diseases of interest and their environment. Approaching general surveillance programs as systems assists with identifying leverage points, including feedback loops and information flow, and the most limiting factor. This information can help target effort and resources to improve program performance. Allocating time and resources to information flow (i.e. sharing knowledge and experiences of people from throughout the program including notifiers, lab and herbarium staff, funding bodies, policy makers and others) builds trust and ownership and facilitates learning and self-organisation. This increases the capacity for innovation, adaptation, and continual improvement, leading to ongoing program benefits. Program management is best supported by a dedicated program coordinator (or coordination team) to carry out monitoring and evaluation, identify challenges and opportunities, and adapt the program. Ensuring that all parts of the program are working together effectively avoids weaknesses in one part causing unintended consequences elsewhere and undermining its overall effectiveness.